P‐139: The Investigation of Field Sequence Color Liquid Crystal Display with New Polymer Stabilized Vertical Alignment Mode. Issue 1 (30th May 2018) - Chen, Xingwu; Gao, Jian; Qiu, Yonyuan; Zhou, Juan; Lan, Song; Tseng, Te-Jen; Chen, Hsiao-Hsien; Hsieh, Chung-Ching; Lin, His-Chien; Lee, Yung-Jui
Abstract : In this paper, a field‐sequential‐color liquid crystal display (FSC LCD) based on new polymer stabilized vertical alignment (N‐PSVA) liquid crystal display mode and photo alignment technology have been developed. An excellent response time of the device can be obtained by the developed of N‐PSVA LC and the optimizing of process, with the operating voltage keep in 10V. By this work, the 32 inch large size FSC TV panels were presented